Rebuilding fictions: Violence and the aesthetic in Cormac McCarthy, Michael Ondaatje, Toni Morrison, and Philip Roth - Lanham, A (2015)
Critical accounts of postmodern fiction, with its inconclusive plots and fractured psyches, typically hinge on tropes of entropy, decentering, and the evacuation of meaning. Recent philosophical debates about ethics and religion, especially in their uptake by the literary academy as postsecular criticism and the ethical turn, deploy a similar set of concepts to emphasize ontological instability and radical deferral to the future as the basic structure of belief and attempts to behave ethically toward others. Focusing on such questions of belief and ethics, Rebuilding Fictions argues for an alternative understanding of postmodern fiction that hinges on tropes not of disintegration but of reconstruction and reintegration. A major strand of postmodern fiction epitomized by the U.S. and Canadian novelists Cormac McCarthy, Michael Ondaatje, Toni Morrison, and Philip Roth obsessively depicts both the violent collapse of lives and societies and the often post-traumatic process of trying to put those lives back together and start over again. Especially in their novels from the early 1990s to the present, McCarthy, Ondaatje, Morrison, and Roth repeatedly describe their characters' lives through metaphors of wounded trees growing back or ruined buildings being rebuilt. Rebuilding Fictions frames this emphasis on reconstruction in the historical period stretching from the tail end of the Cold War through the inter-war 90s to the present global formation of the War on Terror: reconstruction takes center stage in novels concerned with what it means to act in a post-war moment (post-1945, post-1989) or within a war that seems repetitively stuck in previous violence (World War II, the Second Gulf War). Rebuilding Fictions works out the mechanics by which literary characters placed in such violent situations reconstitute their identities, worldviews, and communal ties with others, typically by reading and writing. And these reconstructive acts of reading and writing also rebuild ethical relationships and religious beliefs, portraying belief and ethics not as radically deferred but as simultaneously present and reinventing themselves.